1990
DOI: 10.4141/cjas90-099
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF A 28-DAY SUSTAINED-RELEASE FORMULATION OF RECOMBINANT BOVINE SOMATOTROPIN (rbST) ADMINISTERED TO COWS OVER TWO CONSECUTIVE LACTATIONS

Abstract: LBoNano, M., Gnllo, M., Gallo, G. eNt Br-ocr, E. 1990. Effects of a28-day sustained-release formulation of recombinant bovine somatotropin (rbST)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Structurefunction diversity for bovine GH has also been implied by studies which have detected point mutations in the bovine GH molecule (Lucy et al 1993). Molecular genetic studies have confirmed that considerable polymorphism exists in the gene that encodes bovine GI{ (Cowan et al 1989;Theilmann et al 1989;Kirkpatrick1992 Rocha et al 1992Zhanget al 1993) and studies designed to determine GH genotype-production associations have been initiated (Hilbert et al 1989;Hoj et al 1993;Lucy et al 1993 (Bauman et al 1989a;Oldenbroek et al 1989;L6onard et al 1990). Regardless ofthe potential for cyclical milk response over multiple sustained release injection periods, average lactational milk yield increases of 10-15% are reported in response to this form of rbGH.…”
Section: Production Performance Of Dairy Cows Treated With Growth mentioning
confidence: 98%
See 4 more Smart Citations
“…Structurefunction diversity for bovine GH has also been implied by studies which have detected point mutations in the bovine GH molecule (Lucy et al 1993). Molecular genetic studies have confirmed that considerable polymorphism exists in the gene that encodes bovine GI{ (Cowan et al 1989;Theilmann et al 1989;Kirkpatrick1992 Rocha et al 1992Zhanget al 1993) and studies designed to determine GH genotype-production associations have been initiated (Hilbert et al 1989;Hoj et al 1993;Lucy et al 1993 (Bauman et al 1989a;Oldenbroek et al 1989;L6onard et al 1990). Regardless ofthe potential for cyclical milk response over multiple sustained release injection periods, average lactational milk yield increases of 10-15% are reported in response to this form of rbGH.…”
Section: Production Performance Of Dairy Cows Treated With Growth mentioning
confidence: 98%
“…Growing heifers show lesser insulin resistance and lower milk yield responses to rbGH than multiparous cows (Chilliard 1988) (Gallo 1989;Gallo and Block 1990a) (Fig. 3), it also appears to allow overall adaptation of metabolism such that the incidence of ketosis and liver disease does not increase (reviewed by McBride et al 1988;Burton and McBride 1989;Chilliard 1989 Elvinger et al 1988;Cleale et al 1989;Hansen et al 1989;McDaniel et al 1989;Burton et al 1990b;Gibson et al 1990), increased number of services per conception (by 0.5-1), and a lower conception rate (by 5-10%) in rbGHtreated versus control cows Huber et al 1988;L6onard et al 1990). These trends were especially noticeable when higher doses (> 40 mg d-') of rbGH were used (Thomas et al 1987), but were not statistically significant perhaps due to the limited number of cows and the large variation among treatment groups in these individual trials.…”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 99%
See 3 more Smart Citations